Physiological and sensorial quality of Arabica coffee subjected to different temperatures and drying airflows - Alves, Guilherme Euripedes; Borém, Flávio Meira; Isquierdo, Eder Pedroza; Siqueira, Valdiney Cambuy; Cirillo, Marcelo Ângelo; Pinto, Afonso Celso Ferreira (Acta Scientiarum. Agronomy, 2017)
The objective of this study was to evaluate the correlation between a group of physiological variables (electrical conductivity, potassium leaching, and germination percentage) and a group of drying kinetics variables (drying time and drying rate) in addition to verifying the relation between drying kinetics variables and coffee quality as a function of processing type, temperature, and drying airflow. Coffee drying was conducted in a fixed-layer dryer at two temperatures and two airflows. After drying, an evaluation of the physiological and sensorial quality was conducted. Based on the results obtained, the following conclusions were drawn: coffee that is processed via a dry method is more sensitive to mechanical drying with heated air than coffee processed via a wet method, resulting in poor physiological performance; airflow does not interfere with the physiological quality of pulped and natural coffees; a temperature increase from 40 to 45°C resulted in a decrease in the physiological quality only for pulped coffee; and an increase in the drying rate as a result of an increase in the drying temperature to 40°C had a negative effect on the sensorial quality of pulped coffee.